Principal as an Agent of Change in Improving Educators' Human Resources at MTS Al-Washliyah Tembung - Fadilla, Hasana; Chaniago, Nasrul Saykur (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This article examines the role of the Principal as an agent of change in human resource change management to improve the quality of educators' human resources, which are required to encourage innovation and progress in all aspects of education actively. This is due to several factors that influence the development of education, where dynamic and rapid changes demand the active role of the Principal as a motivator, leader, and director of human resources in schools. This research uses case study qualitative research, data obtained through in-depth interviews with administrators and members of MTs Al-Washliyah Tembung, participant observation, and documentation. Data analysis of this research uses Miles & Huberman, namely with three stages, namely (a) data condensation, (b) data display, and (c) conclusion drawing. The results of this study show that principals can create schools that can adapt to the dynamics of change, create an inspiring learning environment by producing superior educational human resources, and are ready to face future challenges. This research recommends. Strengthening the Principal's Role in Implementing Innovative Strategies in Change Management and Promoting Collaboration and Communication: This recommendation includes developing and implementing innovative programs that promote human resource development and create a collaborative culture in schools through the development of open communication and teamwork.